Ray Omodei interviewed by Bill Stephens in 2012 - Omodei, Ray, 1936-2020.; Stephens, Bill, 1936- (2012)
Ray Omodei talks about his parents; his siblings; his childhood; his schooling and education; his memories of his boarding house and surrounds; Catholic nuns and brothers that influenced his life; his early involvement in theatre; Kalgoorlie Repertory Company; journalism; his role models and artistic influences; Nijinsky; his National Service; London, England; Royal Shakespeare Company; The Hole In the Wall Theatre, Perth, WA; National Theatre Company, Perth; the art of playwriting; Dorothy Hewett; Bonbons and Roses for Dolly; his appointment as Resident Director of Old Tote Theatre Company, Glebe, NSW; Sydney Opera House; his project with the W.A. Education Department; Curtin University; West Australian Academy of the Performing Arts; his appointment as Artistic Director of the Perth State Theatre Company; the new home for The Hole in the Wall; establishing the subscription season concept; the type of plays he likes directing; the funding of emerging theatre companies; his final three years at The Hole in the Wall; opening nights for Shirley Valentine.
Air conditioner noise in the background during the interviews.
Recorded between 20 and 22 February 2012 in Perth, W.A.
Digital master available
Timed summary (22 p.) and uncorrected transcript (typescript, 302 leaves) available.
Keywords: Omodei, Ray, -- 1936-2020. -- Interviews; Theatrical producers and directors -- Australia -- Interviews; Theatre producers and directors